The implementation of podcast as a learning tool in UiTM’s Mandarin Course / Tan Teow Ghee ... [et al.] - Tan, Teow Ghee; Lim, Teck Heng; Goii, Chin Shuanc (2012)
This study attempts to examine use of podcasts in the teaching and learning of Mandarin as a third language in UiTM. It aims to provide an account of the students’ perception towards the content, design and benefits of using the Mandarin Leaming Podcast, which was self-developed, as a supplementary tool in learning Mandarin. It also strives to investigate whether the achievement of students who use the podcasts is better than that of the students who do not use them. Finally, an attempt to examine the relationship between the students’ degree of satisfaction towards Mandarin Leaming Podcast and their achievement in Mandarin is also made. The study was carried out in two phases involving two different batches of students. In the first phase the subjects in the experimental group were told to utilize the podcasts in their study, while in the second phase, the subjects were students who voluntarily utilized the podcasts. The data collected were examined after both phases. The results indicate that the students were of the opinion that the content and design of the podcasts were appropriate, and that the podcasts were suitable for them to use as a supplementary learning tool. They also claimed that it was beneficial for them to use the podcasts. The findings suggest that students who utilized the podcast obtained better achievement than those who did not. However, there is no significant correlation between the degree of satisfaction and their achievement. The conclusion made is podcast-based learning can be beneficial to students and thus should be implemented in the teaching and learning of Mandarin as a third language.